White dwarfs, black holes and the philosophical incommensurability thesis - Rivadulla, Andrés (Revista de Humanidades de Valparaíso, 2013)
Incommensurability has been for about forty years one of the most discussed topics on the contemporary philosophy of science. In order to tackle this issue I assume Howard Sankey’s (1997: 425) characterization of incommensurability as “the thesis that the content of some alternative scientific theories is incomparable due to translation failure between the vocabulary the theories employ”. This kind of incomparability should pre- vent for instance the derivation of Newtonian mechanics from relativity theory, as Thomas Kuhn (1970a and 1970b) maintains. Since I have myself been concerned with the comparison of Newtonian and Einsteinian mass concepts in Rivadulla (2004), I focus in this short paper on the comparability of theories of contemporary theoretical physics. Thus, instead of dealing with the question of whether the theories of contemporary physics are definitely incommensurable with each other, the main aim of this paper is to provide an answer to the question of whether it makes any sense to think about the in- commensurability between contemporary physical theories, due to their obvious comparability.